PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA ANGGOTA ORGANISASI NIRLABA (STUDI PADA AIESEC SURABAYA) - DWI PERMANA, ERWIN (Jurnal Akuntansi AKUNESA, 2016)
Abstract This study aims to examine the effect of organizational culture, motivation, and job satisfaction on the performance of non-profit organization AEISEC Surabaya. The study was conducted using a questionnaire survey. Samples was collected using simple random method. Questionnaires distributed to 40 respondents, but only 33 data that can be examined. Data were analyzed using multiple regression. The results showed that: organizational culture does not affect the performance of member organizations, motivation does not affect the performance of member organizations, and job satisfaction has an affect on the performance of member organizations. Keywords: Organizational Culture, Motivation, Job Satisfaction, Performance